Building Character Education in Rumi Children in Sumur Batu Village, Bantar Gebang – Bekasi City, West Java, Indonesia - Darmeinis, Darmeinis; Siahaan, Leroy Holman; Novena, Theresia; Sinta, Putri; Sunandar, Karen; Tarigan, Roy Firdaus Johanta; Kusmiati, Kusmiati; Milasari, Hesti Okta (Jurnal Pengabdian Masyarakat Formosa, 2024)
Character education in early childhood is an effort to instill commendable behavior in children, both behavior in worship, behavior as a good citizen, behavior in interacting with other people and the environment, and commendable behavior that is beneficial for their success in life. Character education is implemented in every environment where children are. The family environment is the first environment that children find. Parents have the responsibility to instill good attitudes in children. Parents should not leave their children's character education to the teachers. Parents and teachers are models that children will imitate and emulate, both in words and deeds. Character development in children can be done through advice, habituation, modeling, and reinforcement.